The Importance of Emotional Development in Early Childhood through Group Activities: A Literature Review at TK Negeri 6 Samatiga - yulidar ubbg (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This literature review explores the significance of emotional development in early childhood, particularly in kindergarten settings, through group activities. Early childhood is a crucial period for emotional growth, as it lays the foundation for children’s future social, emotional, and cognitive development. TK Negeri 6 Samatiga serves as a case study to illustrate how structured group activities enhance emotional intelligence among young children. The review highlights various aspects such as the development of social skills, empathy, self-regulation, confidence, and effective communication. By facilitating interactions in group settings, children learn to manage their emotions and understand the feelings of others, thereby fostering healthy relationships and a supportive learning environment. This research emphasizes the need for educators and parents to recognize the role of group activities in promoting emotional well-being in young learners. In conclusion, the study advocates for the implementation of more collaborative and interactive activities in kindergarten curricula to nurture emotional competence among preschoolers.